Digital Marketing as a Marketing Strategy to Increase SMEs Revenue: Case Study: Uncle Sam’s Cafe And Resto in Lubuk Pakam, Deli Serdang - Rahmadhani, Sophia; Nurbaiti; Dharma, Budi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
In an era of rapid technological advancement, the significance of digital marketing as a pivotal tool for business growth cannot be overstated. Despite its widespread adoption, there are still challenges and fluctuations encountered by businesses, even when employing digital marketing strategies. Understanding the effectiveness of these strategies and identifying areas for improvement is crucial for businesses, particularly Small and Medium-sized Enterprises (SMEs), to thrive in today's competitive market landscape. Therefore, this research endeavors to shed light on the strategies utilized by SMEs, using Uncle Sam’s Cafe And Resto in Lubuk Pakam Deli Serdang as a case study, to enhance their revenue through digital marketing. By delving into this topic, we aim to provide actionable insights and recommendations that can empower SMEs to leverage digital marketing effectively, thereby ensuring their sustainability and growth in the digital age. This study employs a qualitative descriptive method, utilizing data collection techniques such as observation and interviews. Through the application of SWOT analysis (Strengths, Weaknesses, Opportunities, Threats), the research aims to comprehensively analyze the current state of digital marketing strategies employed by Uncle Sam’s Cafe And Resto. By examining the strengths and weaknesses, as well as identifying potential opportunities and threats, this study seeks to offer valuable guidance to SMEs seeking to optimize their digital marketing efforts.